Common and Rare Variants Genetic Association Analysis of Cigarettes per Day Among Ever-Smokers in Chronic Obstructive Pulmonary Disease Cases and Controls. Issue 6 (15th May 2018) - Lutz, Sharon M; Frederiksen, Brittni; Begum, Ferdouse; McDonald, Merry-Lynn N; Cho, Michael H; Hobbs, Brian D; Parker, Margaret M; DeMeo, Dawn L; Hersh, Craig P; Ehringer, Marissa A; Young, Kendra; Jiang, Lai; et al.
Abstract: Introduction: Cigarette smoking is a major environmental risk factor for many diseases, including chronic obstructive pulmonary disease (COPD). There are shared genetic influences on cigarette smoking and COPD. Genetic risk factors for cigarette smoking in cohorts enriched for COPD are largely unknown. Methods: We performed genome-wide association analyses for average cigarettes per day (CPD) across the Genetic Epidemiology of COPD (COPDGene) non-Hispanic white (NHW) ( n = 6659) and African American (AA) ( n = 3260), GenKOLS (the Genetics of Chronic Obstructive Lung Disease) ( n = 1671), and ECLIPSE (the Evaluation of COPD Longitudinally to Identify Predictive Surrogate Endpoints) ( n = 1942) cohorts. In addition, we performed exome array association analyses across the COPDGene NHW and AA cohorts. We considered analyses across the entire cohort and stratified by COPD case–control status. Results: We identified genome-wide significant associations for CPD on chromosome 15q25 across all cohorts (lowest p = 1.78 × 10 −15 ), except in the COPDGene AA cohort alone. Previously reported associations on chromosome 19 had suggestive and directionally consistent associations ( RAB4, p = 1.95 × 10 −6 ; CYP2A7, p = 7.50 × 10 −5 ; CYP2B6, p = 4.04 × 10 −4 ). When we stratified by COPD case–control status, single nucleotide polymorphisms on chromosome 15q25 were nominally associated with both NHW COPD cases (β = 0.11, p = 5.58 × 10 −4 ) and controls (β = 0.12, p = 3.86 × 10 −5 ) For the gene-based exome array association analysis of rare variants, there were no exome-wide significant associations. For these previously replicated associations, the most significant results were among COPDGene NHW subjects for CYP2A7 ( p = 5.2 × 10 −4 ). Conclusions: In a large genome-wide association study of both common variants and a gene-based association of rare coding variants in ever-smokers, we found genome-wide significant associations on chromosome 15q25 with CPD for common variants, but not for rare coding variants. These results were directionally consistent among COPD cases and controls. Implications: We examined both common and rare coding variants associated with CPD in a large population of heavy smokers with and without COPD of NHW and AA descent. We replicated genome-wide significant associations on chromosome 15q25 with CPD for common variants among NHW subjects, but not for rare variants. We demonstrated for the first time that common variants on chromosome 15q25 associated with CPD are similar among COPD cases and controls. Previously reported associations on chromosome 19 showed suggestive and directionally consistent associations among common variants ( RAB4, CYP2A7, and CYP2B6 ) and for rare variants ( CYP2A7 ) among COPDGene NHW subjects. Although the genetic effect sizes for these single nucleotide polymorphisms on chromosome 15q25 are modest, we show that this creates a substantial smoking burden over the lifetime of a smoker.